PEMANFAATAN MEDIA SOSIAL UNTUK IKLAN KAMPANYE PASANGAN CALON PADA PEMILIHAN - Ellisa Vikalista; Atika Atika (Metacommunication: Journal of Communication Studies, 2022)
Due to this continuing and wide-spreading COVID-19 pandemic, the 2020 election processes of the head of governments have been adapting, particularly the campaign processes. This study analysis the utilization of social media in campaign advertisements by candidates of the 2020 Election of the Mayor of Banjarmasin. Research type and approach is descriptive-qualitative. Key informants were mayor candidates both the incumbent and challengers. Additional informants were officers at the Local Election Commission (KPU Banjarmasin) and the Election Surveillance Agency (Bawaslu Banjarmasin). Data obtained from observation, interview and important documents. The research findings showcase that each candidateshave utilized several platform of social media. They reached their followers/voters through          Instagram, Facebook, YouTube and Twitter. Instagram was the most used platform. The candidates often shared photos and videos with caption and hastag, commented on comments and Direct Message (DM), and used IG Story and IG TV to reach out their followers. They often also searched and explored the potential persons or teams to be recruited as campaign team through social media. And also, they used social media to investigate their competitors’ activities.